2013
DOI: 10.1016/j.rboe.2012.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Study: Resistance Comparison of Posterior Antiglide Plate and Lateral Plate on Synthetic Bone Models Simulating Danis-Weber B Malleolar Fractures

Abstract: Objective The purpose of this study was to compare different positions of plates in lateral malleolar Danis-Weber B fractures on synthetic bone: a lateral plate and a posterior antiglide plate. Methods Short oblique fractures of distal fibula at the level of the syndesmosys were simulated with a fibular osteotomy in sixteen synthetic fibula bones (Synbone®). Eight fractures were fixed with lateral plating associated with an independent lag screw, and the other eight wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
6
0
3
Order By: Relevance
“…4 Furthermore, several biomechanical studies have demonstrated improved biomechanical stability and strength with posterior or posterolateral antiglide plates when compared with traditional lateral neutralization plates. 1,7,12 One concern of posterior and posterolateral plating of the fibula is whether the position of the plate causes peroneal tendon irritation resulting in hardware removal. Weber and Krause 9 retrospectively reviewed 70 patients who underwent posterolateral plating of their fibula and found that 43% (30/70) required hardware removal because of peroneal tendon irritation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Furthermore, several biomechanical studies have demonstrated improved biomechanical stability and strength with posterior or posterolateral antiglide plates when compared with traditional lateral neutralization plates. 1,7,12 One concern of posterior and posterolateral plating of the fibula is whether the position of the plate causes peroneal tendon irritation resulting in hardware removal. Weber and Krause 9 retrospectively reviewed 70 patients who underwent posterolateral plating of their fibula and found that 43% (30/70) required hardware removal because of peroneal tendon irritation.…”
Section: Discussionmentioning
confidence: 99%
“…3 Posterior and posterolateral plating is biomechanically advantageous because it directly buttresses against this pull and allows superior distal fixation with bicortical screws. 4,7,8 However, despite its biomechanical superiority, some authors have concern for an increased risk of peroneal tendon injury with posterior and posterolateral plating when compared with lateral plating. No significant differences have been noted between different plating constructs in terms of common complications such as infection, wound dehiscence, hardware failure, or loss of reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Ïîçèö³îíóâàííÿ ïëàñòèíè ç ëàòåðàëüíî¿ ïî-âåðõí³ õàðàêòåðèçóºòüñÿ á³ëüøîþ äåôîðìàö³ºþ òà ìåíøîþ ñòàá³ëüí³ñòþ äî ñêðóòíèõ ñèë. Íàÿâíèé ðèçèê âíóòð³øíüîñóãëîáîâîãî ââåäåííÿ ãâèíòà ÿêèé âàaeêî ïðîêîíòðîëþâàòè çà äîïîìîãîþ ðåíò´åí-îïòè÷íîãî ïåðåòâîðþâà÷à [7]. Âíàñ-ë³äîê íåçíà÷íî¿ òîâùèíè ï³äøê³ðíî¿ aeèðîâî¿ êë³òêîâèíè íàä ëàòåðàëüíîþ ê³ñòî÷êîþ ó ïàö³-ºíò³â ñïîñòåð³ãàºòüñÿ äèñêîìôîðò ïðè íîñ³íí³ çâè÷àéíîãî âçóòòÿ [8] òà óñêëàäíåííÿ ç³ ñòîðîíè ï³ñëÿîïåðàö³éíî¿ ðàíè [7].…”
Section: Abstract: Malleoli Fractures Volkmann's Triangle Osteosynunclassified
“…Íàÿâíèé ðèçèê âíóòð³øíüîñóãëîáîâîãî ââåäåííÿ ãâèíòà ÿêèé âàaeêî ïðîêîíòðîëþâàòè çà äîïîìîãîþ ðåíò´åí-îïòè÷íîãî ïåðåòâîðþâà÷à [7]. Âíàñ-ë³äîê íåçíà÷íî¿ òîâùèíè ï³äøê³ðíî¿ aeèðîâî¿ êë³òêîâèíè íàä ëàòåðàëüíîþ ê³ñòî÷êîþ ó ïàö³-ºíò³â ñïîñòåð³ãàºòüñÿ äèñêîìôîðò ïðè íîñ³íí³ çâè÷àéíîãî âçóòòÿ [8] òà óñêëàäíåííÿ ç³ ñòîðîíè ï³ñëÿîïåðàö³éíî¿ ðàíè [7]. Ïðè çàñòîñóâàíí³ çàäíüîãî äîñòóïó äàíå óñêëàäíåííÿ âèêëþ÷àºòüñÿ, ùî íàäຠìîaeëèâ³ñòü âèêîðèñòàííÿ á³êîðòèêàëüíèõ ãâèíò³â, ÿê³ çàáåçïå÷óþòü á³ëüøó ñòàá³ëü-í³ñòü [7].…”
Section: Abstract: Malleoli Fractures Volkmann's Triangle Osteosynunclassified
See 1 more Smart Citation